NEGOSIASI MUKA MASYARAKAT DESA BEDA KEYAKINAN Studi Interaksi Masyarakat Berbasis Keyakinan (Nahdlatul Ulama, Muhammadiyah, dan Majlis Tafsir Al-Qur’an) di Dusun Pakelrejo, Desa Piyaman, Wonosari, Gunung Kidul) - Siti Fauziyah (Jurnal Sosiologi Agama, 2017)
In Indonesia, one of the problems faced by religious people is religious conflict. When Islam entered the island of Java, Islam had to deal with local Javanese beliefs. In spreading the teachings of Islamic renewal and then bring up cultural clashes that cause tension then even conflict between supporters of puritan groups with syncretic Islam. This happened in Dusun Pakelrejo Desa Piyaman, when the Majlis Tafsir Al-Qur’an (MTA) tried to maintain its existence to be accepted by the wider community especially by Muhammadiyah and NU adherents. The MTA uses a negotiation advance with Postheistic patterns. In this case, Postheistik becomes a new pattern of face transactions to build cooperation and mutual need without seeing one’s self-confidence. Therefore, post-theistic communication becomes a phenomenon of interfaith relations.Keywords: Negotiations Advance, Bina Peace, Postheistik